ADAPTABILITY AND STABILITY OF SPRING BARLEY CULTIVARS IN TERMS OF PERFORMANCE - Солонечний, П. М. (Scientific Progress & Innovations, 2014)
The results of ecological trials of 17 spring barley cultivars bred at the Plant Production Institute named after V.Ya. Yuryev NAAS are presented in the article. Environment effect, genotype effect and genotype x environment interaction effect on the formation of seed weight (performance of plants) were estimated. Peculiarities of environments across ecological trial plots as backgrounds for genotype assessment were established. Cultivars with high general and specific adaptability by plant performance as valuable source material for spring barley breeding were identified.